Community detection in the sparse hypergraph stochastic block model. Issue 3 (14th March 2021) - Pal, Soumik; Zhu, Yizhe
Abstract: We consider the community detection problem in sparse random hypergraphs. Angelini et al. in [6] conjectured the existence of a sharp threshold on model parameters for community detection in sparse hypergraphs generated by a hypergraph stochastic block model. We solve the positive part of the conjecture for the case of two blocks: above the threshold, there is a spectral algorithm which asymptotically almost surely constructs a partition of the hypergraph correlated with the true partition. Our method is a generalization to random hypergraphs of the method developed by Massoulié (2014) for sparse random graphs.